Psychophysiological stress in athletes across concussion recovery milestones. Issue 11 (25th May 2017) - Mainwaring, Lynda; Senthinathan, Arrani; Hutchison, Michael; Thomas, Scott; Richards, Doug; Churchill, Nathan
Abstract : Background: Psychophysiological stress markers across concussion recovery milestones have not been examined in an integrated study. Objective: To examine physiological (heart rate variability [HRV] and salivary cortisol) and psychological (mood, perceived stress, symptoms, and sleep quality) factors of stress in concussed athletes across clinical recovery milestones. Design: A prospective case control repeated measures study was conducted over three clinical recovery milestones: Symptomatic (acute), Asymptomatic, and 1-week Post Return-to-Play (RTP). Setting: Single university athlete program monitored by the university's sport medicine clinic, Ontario, Canada. Participants: Male and female varsity athletes (n=26; M=16, F=10) with medically diagnosed concussion and their matched controls (n=26; M=16, F=10). Outcome measures: Physiological: HRV and salivary cortisol; psychological: mood, perceived stress, sleep quality and symptoms. Main results: Univariate analyses identified a group by sex interaction for specific HRV measures (RR intervals p=0.0084, Low frequency Power p=0.0084, Mean Heart Rate p=.0049, and Low/High Frequency Ratio p=0.0084). Multivariate analyses of HRV identified main effects for sex and group, and a significant interaction with reduced HF HRV for female concussed athletes through to 1-week post RTP (FDR=.05). HRV suppression was related to mood disturbance in males (FDR.05). Psychological measures were significantly worse for concussed athletes relative to controls at the Symptomatic Phase, but significantly better at 1-week post RTP (paired Wilcoxon at FDR=.05). Funding disclosure: This study was supported by a grant from the Canadian Institute of Health Research (CIHR) −2012-ABI-CAT1-971 to L. Mainwaring. Conclusions: For both males and females, mood disturbance, symptoms, and sleep quality perturbations were resolved by 1-week post RTP whereas autonomic nervous system disruption persisted beyond RTP in females. Psychophysiological non-invasive markers show promise for concussion monitoring. Competing interests: None.